Environmental and spatial modeling of the critically endangered sand tiger shark, Carcharias taurus, in the Southwest Atlantic Ocean - Mayer, Guilherme Burg; Freitas, Renato Hajenius Aché de; Charvet, Patricia; Laporta, Martín; Mas, Federico; Montealegre-Quijano, Santiago [UNESP]; Paesch, Laura; Palacio, María Cecilia; Pereyra, Inés; Riverón, Sabrina; Rolim, Fernanda Andreoli; Silveira, Santiago; et al. (Springer Nature, 2025)
The sand tiger shark (Carcharias taurus) is a critically endangered species, whose spatial ecology in the Southwest Atlantic Ocean remains poorly understood. This study is the first regional attempt to elucidate the habitat conditions linked to the distribution and occurrence of this migratory coastal shark, using the largest regional dataset for the Southwest Atlantic. An ensemble of species distribution models was applied to assess various environmental predictors of habitat suitability for C. taurus. Our occurrence data was obtained throughout the species’ distribution range along Brazil, Uruguay, and Argentina. These data were compiled mainly from artisanal and recreational fishing records, and are linked to research, reporting efforts and projects. Results indicated that bathymetry, bottom temperature, primary productivity, and salinity were important environmental factors linked to the species occurrence and suitable habitats. These factors were mainly associated with coastal and estuarine habitats. Areas with high suitability for C. taurus were identified in Northern Argentina, the entirety of the La Plata River estuarine mouth and extended shelf, between Uruguay and Southern Brazil, and Southeast Brazil, indicating these subregions as priority areas for the species’ conservation. Ensemble forecasting projections showed a habitat suitability retraction in colder months for southern latitudes. Our study also gathered novel insights on the species' biology and occurrence from unpublished data.
Keywords: Chondrichthyes; Conservation; Distribution models; Spatial ecology; Spatial planning; Species distribution